THE ROLE OF TEACHERS IN MAKING INCLUSIVE EDUCATION A SUCCESS IN REGULAR SCHOOLS - Asyiqoh, Durroh; Mundiri, Akmal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Inclusive education is an approach that aims to provide equal access to education for all children, including students with special needs. This approach emphasizes respect for diversity and equality of learning opportunities without discrimination. This study aims to identify the role of teachers in the success of inclusive education in regular schools, including professional, pedagogical, social, and personal competencies. The research method uses a qualitative approach with in-depth interview techniques, observation, and document studies. The research was conducted in Indonesia, where inclusive education is increasingly strengthened as part of expanding access to education and implementing the principle of equality. The study results show that teachers are essential in creating an inclusive learning environment. This is done through curriculum adaptation, differentiated learning methods, and classroom management that encourages collaboration between regular students and students with special needs. In addition, training and support from schools and the government are key factors in increasing teacher capacity. Teachers not only act as teachers but also as facilitators, motivators, and mentors who help student development. This study emphasizes the importance of teachers as the vanguard in inclusive education. Effective implementation requires competent teachers and is supported by a supportive education ecosystem. These findings contribute to developing inclusive education policies and practices, particularly in improving Indonesia's quality of inclusive and equitable learning.